Hemostatic nano hydrogel particle as well as preparation method and application thereof
By developing a hemostatic nanohydrogel particle composed of mesoporous silica nanoparticles, thrombin, methacrylamide gelatin and photoinitiator, the thrombin hemostatic material has been solved by reducing activity and blood clots in the digestive tract environment. The problem of instability achieves a fast, lasting and stable hemostatic effect.
Patent Information
- Application Number
- CN202411388199.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
AI Technical Summary
The existing thrombin hemostasis materials have weakened their activity in the extreme environment of the digestive tract, making it difficult to stay at the bleeding site, and the initial blood clots are unstable, which can easily lead to rebleeding.
A hemostatic nanohydrogel particle was developed to quickly stop hemostatic by blue laser cross-linking, which has strong tissue adhesion and can maintain thrombin activity under acid and alkaline conditions. The particles consist of mesoporous silica nanoparticles, thrombin, methacrylamide gelatin and photoinitiator.
It achieves rapid hemostasis, enhances the stability and durability of blood clots, reduces the risk of rebleeding, and maintains effectiveness in different acid and alkaline environments.
Smart Images

Figure BDA0005072054440000071 
Figure BDA0005072054440000081 
Figure BDA0005072054440000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to hemostatic nano hydrogel particles and a preparation method and application thereof. Background Art
[0002] Thrombin and fibrin are often used as the main active ingredients in hemostatic materials, which can directly activate the coagulation cascade reaction pathway to promote the coagulation process to form blood clots. Compared with organic and inorganic hemostatic materials, coagulation factors can better promote the formation of insoluble fibrin and have a hemostatic ability that other materials cannot achieve. At the same time, as a bioactive substance, it has good degradability and accelerates wound repair. Therefore, it is widely developed and applied in hemostatic materials.
[0003] However, there are still some deficiencies in the use of thrombin hemostatic materials: 1. The coagulation activity of thrombin is weakened when it is directly exposed to the extreme environment of the digestive tract; 2. Most of the thrombin solution cannot stay at the bleeding site to play a hemostatic role; 3. The initially formed blood clot is not stable enough, and it is easy to bleed again when it breaks or falls off. For example, after gastrointestinal surgery hemostasis, if there is a large amount of gastrointestinal peristalsis, rebleeding may occur. Therefore, it is of great significance to develop a hemostatic material with fast coagulation speed, tissue adhesion, the ability to maintain thrombin activity under acid-base conditions, long-lasting hemostatic effect, and good biocompatibility. Summary of the invention
[0004] In view of the problem that the thrombin in the currently used thrombin hemostatic materials is directly exposed to the digestive tract environment and its coagulation activity is weakened, most of the thrombin solution cannot stay at the bleeding site to play a hemostatic effect, and the initially formed blood clot is not stable enough and is prone to re-bleeding when it is lysed or falls off, the present invention proposes a hemostatic nano-hydrogel particle and a preparation method and application thereof. The hemostatic nano-hydrogel particle of the present invention can quickly stop bleeding through blue laser cross-linking, has strong tissue adhesion, and can maintain thrombin activity under acid-base conditions, thereby improving the hemostatic effect and reducing the risk of re-bleeding.
[0005] Specifically, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a hemostatic nano-hydrogel particle, characterized in that the hemostatic nano-hydrogel particle is prepared from the following raw materials in parts by weight: 40-50 parts of mesoporous silica nanoparticles, 20-33 parts of thrombin, 25-50 parts of methacrylamide-based gelatin and 0.5-1.25 parts of a photoinitiator.
[0007] Preferably, the hemostatic nano-hydrogel particles are characterized in that the hemostatic nano-hydrogel particles are prepared from the following raw materials in parts by weight: 43-47 parts of mesoporous silica nanoparticles, 25-30 parts of thrombin, 30-40 parts of methacrylamide-based gelatin and 0.8-1 part of a photoinitiator.
[0008] Preferably, the hemostatic nano-hydrogel particles are characterized in that the mesoporous silica nanoparticles are selected from one of spherical mesoporous silica nanoparticles, dendritic mesoporous silica nanoparticles and hollow mesoporous silica nanoparticles;
[0009] And / or, the mesoporous silica nanoparticles are selected from one of the MCM series, SBA series, MSU series and TDU series;
[0010] Preferably, the mesoporous silica nanoparticles are selected from amino-modified dendritic mesoporous silica nanoparticles.
[0011] Preferably, the hemostatic nano-hydrogel particles are characterized in that the thrombin is selected from one of porcine thrombin, bovine thrombin and human thrombin;
[0012] Preferably, the hemostatic nano-hydrogel particles can maintain thrombin activity for ≥45 days.
[0013] Preferably, the hemostatic nano-hydrogel particles are characterized in that the amino substitution degree of the methacrylamide-based gelatin is 30-90%;
[0014] Preferably, the amino substitution degree of the methacrylamide-based gelatin is 60-90%.
[0015] Preferably, the hemostatic nano-hydrogel particles are characterized in that the photoinitiator is selected from one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-40-(2-hydroxyethoxy)-2-methylpropenone (IC-2959), 2,2'-azo [2-methyl-n-(2-hydroxyethyl) propionamide (VA086), triethanolamine (TEA), N-vinyl caprolactam (VC) and eosin-y (EY);
[0016] Preferably, the photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0017] Preferably, the hemostatic nano-hydrogel particles are characterized in that the triggering light source of the hemostatic nano-hydrogel particles is a blue laser with a wavelength of 395-425nm, a white light with a wavelength of 300-760nm, or an ultraviolet light with a wavelength of 200-400nm;
[0018] Preferably, the triggering light source of the hemostatic nano-hydrogel particles is a blue laser with a wavelength of 395-425 nm.
[0019] In a second aspect, the present invention provides a method for preparing the hemostatic nano-hydrogel particles, the method comprising the following steps:
[0020] (1) mixing mesoporous silica nanoparticles and thrombin and dissolving them in pure water, and then performing ultrasonic treatment and stirring treatment to obtain a mesoporous silica nanoparticle solution loaded with thrombin;
[0021] (2) dissolving methacrylamide-based gelatin and a photoinitiator in a solvent to obtain a GelMA premix;
[0022] (3) The thrombin-loaded mesoporous silica nanoparticle solution is mixed with the GelMA premix, and the mixture is stirred after ultrasonic treatment, and the precipitate is collected by centrifugation to obtain hemostatic nano-hydrogel particles.
[0023] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (1), the concentration (g / ml) of the thrombin-loaded mesoporous silica nanoparticle solution is 12-16.6%;
[0024] Preferably, the concentration (g / ml) of the thrombin-loaded mesoporous silica nanoparticle solution is 13.6-15.4%;
[0025] Further preferably, the mesoporous silica nanoparticles and thrombin are mixed in a mass ratio of 1:(2-2.44).
[0026] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (1), the ultrasonic treatment time is 25-35 min;
[0027] and / or, the power of ultrasound is 40-45 khz;
[0028] Preferably, the stirring time is 25-35 min.
[0029] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (2), the solvent is selected from one of pure water, physiological saline and phosphate buffer.
[0030] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (2), the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 5-30%;
[0031] Preferably, the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 5-10%;
[0032] More preferably, the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 6-8%.
[0033] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (2), the concentration (g / ml) of the photoinitiator in the GelMA premix is 0.10%-0.40%;
[0034] Preferably, the concentration (g / ml) of the photoinitiator in the GelMA premix is 0.16-0.25%.
[0035] Preferably, in the method for preparing the hemostatic nano-hydrogel particles, in step (3), the mesoporous silica nanoparticle solution loaded with thrombin is mixed with the GelMA premix solution in a volume ratio of 1:2 to 2:1;
[0036] Preferably, the mesoporous silica nanoparticle solution loaded with thrombin is mixed with the GelMA premix solution in a volume ratio of 1:1;
[0037] Further preferably, the ultrasonic treatment time is 25-35 min;
[0038] and / or, the power of ultrasound is 40-45 khz;
[0039] More preferably, the stirring time is 6-7h.
[0040] In a third aspect, the present invention provides hemostatic nano-hydrogel particles prepared by the method for preparing hemostatic nano-hydrogel particles.
[0041] In a fourth aspect, the present invention provides a hemostatic system, characterized in that the hemostatic system comprises the hemostatic nano-hydrogel particles, a hemostatic nano-hydrogel particle injection device and a triggering light source generating device.
[0042] Preferably, the hemostatic system is characterized in that the hemostatic nano-hydrogel particle injection device comprises a syringe and a digestive endoscope channel;
[0043] Preferably, the triggering light source generating device includes a blue laser emitting lamp, a blue laser endoscope, a narrow-band imaging endoscope and an ultraviolet light emitting lamp.
[0044] In a fifth aspect, the present invention provides use of the hemostatic nano-hydrogel particles in the preparation of hemostatic materials or drugs.
[0045] In a sixth aspect, the present invention provides the use of the hemostatic nano-hydrogel particles in the preparation of organ hemostatic materials or drugs.
[0046] Preferably, the application is characterized in that the organ is a solid organ or a hollow organ;
[0047] Preferably, the solid organ is heart, liver, spleen, lung, pancreas or kidney;
[0048] More preferably, the hollow organ is the esophagus, stomach, duodenum, jejunum, ileum or colon.
[0049] Beneficial effects of the present invention:
[0050] The hemostatic nano hydrogel particles of the present invention can quickly stop bleeding through blue laser cross-linking, have strong tissue adhesion, and can maintain thrombin activity under acid-base conditions, thereby improving the hemostatic effect and reducing the risk of rebleeding. They can be used for solid organs such as the heart, liver, spleen, lungs or kidneys, and hollow organs such as the esophagus, stomach, duodenum, jejunum, ileum or colon, and can maintain thrombin activity for ≥45 days after freeze-drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 Shown are transmission electron micrographs of the hemostatic nanohydrogel particles prepared in Example 1-1, wherein A is an amino-modified dendritic mesoporous silica nanoparticle; B is an amino-modified dendritic mesoporous silica nanoparticle loaded with thrombin; C is an amino-modified dendritic mesoporous silica loaded with thrombin encapsulated by GelMA; and D is an amino-modified dendritic mesoporous silica loaded with thrombin encapsulated by GelMA after blue light excitation.
[0052] Figure 2 Shown are the loading rate and encapsulation rate of the mesoporous silica and thrombin prepared in Example 1-1.
[0053] Figure 3 Shown is the Zeta potential diagram of the hemostatic nano-hydrogel particles prepared in Example 1-1.
[0054] Figure 4 The following are the coagulation effect diagrams of different materials mixed with fresh blood in Experimental Example 1. A is the coagulation effect diagram of blood mixed with physiological saline; B is the coagulation effect diagram of blood mixed with thrombin solution; C is the coagulation effect diagram of blood mixed with amino dendritic mesoporous silica; D is the coagulation effect diagram of blood mixed with amino dendritic mesoporous silica loaded with thrombin; E is the coagulation effect diagram of blood mixed with amino dendritic mesoporous silica loaded with thrombin wrapped in the outer ring of GelMA after UV cross-linking.
[0055] Figure 5The following are scanning electron microscope images of blood clots formed after different materials were mixed with fresh blood in Experimental Example 1. A is a scanning electron microscope image of a blood clot formed after blood was mixed with normal saline; B is a scanning electron microscope image of a blood clot formed after blood was mixed with thrombin solution; C is a scanning electron microscope image of a blood clot formed after blood was mixed with amino dendritic mesoporous silica; D is a scanning electron microscope image of a blood clot formed after blood was mixed with amino dendritic mesoporous silica loaded with thrombin; E is a scanning electron microscope image of a blood clot formed after blood was mixed with amino dendritic mesoporous silica loaded with thrombin wrapped in an outer ring of GelMA and then cross-linked by ultraviolet light.
[0056] Figure 6 The figure shows the coagulation initiation time after different materials are mixed with normal blood in Experimental Example 2; A is a diagram showing the coagulation effect of different materials initiating coagulation; and B is a statistical diagram showing the coagulation time of different materials.
[0057] Figure 7 The figure shows the coagulation initiation time after different materials are mixed with the blood of patients with liver cirrhosis in Experimental Example 2; A is a diagram of the coagulation effect of different materials initiating coagulation; B is a statistical diagram of the coagulation time of different materials.
[0058] Figure 8 Shown are the coagulation effect diagrams of different materials in Experimental Example 3 after being treated with simulated gastric juice and intestinal juice; A is the coagulation effect diagram of different materials after being treated with simulated gastric juice; B is the coagulation effect diagram of different materials after being treated with simulated intestinal juice.
[0059] Fig. 9 Shown are the experimental results of different materials used for rat liver hemostasis in Experimental Example 4; A is a picture of an untreated wound; B is a picture of a wound after application of thrombin solution; C is a picture after application of hemostatic nano-hydrogel particles and blue laser cross-linking treatment; DF are scanning electron microscopy results of ex vivo liver tissue wound specimens after hemostasis.
[0060] Fig.10 The following are the effects of different materials used in miniature pigs to stop bleeding under endoscopy with blue laser in Experimental Example 5. A is a picture showing the effect of stopping bleeding in the esophagus; B is a picture showing the effect of stopping bleeding in the stomach; and C is a picture showing the effect of stopping bleeding in the duodenum.
[0061] Fig.11 Shown is a schematic diagram of the principle of cross-linking reaction produced by light-excited photoinitiator.
[0062] Fig.12 Shown is a diagram showing the effect of thrombin activity after freeze-drying of the hemostatic nano-hydrogel particles in Experimental Example 6. DETAILED DESCRIPTION
[0063] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments.
[0064] The invention provides a hemostatic nano hydrogel particle, which is prepared by including the following raw materials in parts by weight: 40-50 parts of mesoporous silica nanoparticles, 20-33 parts of thrombin, 25-50 parts of methacrylamide-based gelatin and 0.5-1.25 parts of a photoinitiator.
[0065] In some specific embodiments, the weight proportion of the mesoporous silica nanoparticles in the hemostatic nano-hydrogel particles can be any two values between 40-50: 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50.
[0066] In some specific embodiments, the weight proportion of thrombin in the hemostatic nano-hydrogel particles can be any two values between 20-33: 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, or 33.
[0067] In some specific embodiments, the weight proportion of methacrylamide-based gelatin in the hemostatic nano-hydrogel particles can be any two values between 25-50: 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50.
[0068] In some specific embodiments, the weight proportion of the photoinitiator in the hemostatic nano-hydrogel particles can be any two values between 0.5-1.25: 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2 or 1.25.
[0069] In some specific embodiments, the amino substitution degree of methacrylamide-based gelatin (GelMA) is 30-90%, and the molecular weight is 100-200kD. The amino substitution degree is the proportion of amino groups in gelatin replaced by methacrylate groups during the synthesis of methacrylamide-based gelatin (GelMA). Under the same conditions, the higher the substitution degree, the stronger the strength of the cured GelMA hydrogel.
[0070] In some specific embodiments, the photoinitiator is selected from one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-40-(2-hydroxyethoxy)-2-methylpropenone (IC-2959), 2,2'-azo [2-methyl-n-(2-hydroxyethyl) propionamide (VA086), triethanolamine (TEA), N-vinyl caprolactam (VC) and eosin-y (EY); the initiating light source is a blue laser with a wavelength of 400 to 420 nm, a white light with a wavelength of 300 to 500 nm, or an ultraviolet light with a wavelength of 200 to 400 nm.
[0071] The principle of cross-linking reaction of photoinitiator: During the photo-cross-linking process, the photoinitiator absorbs light energy of a specific wavelength and is excited to an excited state, which will produce active substances such as free radicals or ions. The above substances will trigger the cross-linking reaction of the acrylic acid group in methacrylamide gelatin (GelMA), thereby forming a three-dimensional network structure. The reaction is as follows: Fig.11 shown.
[0072] Unless otherwise specified, the various reagents / instruments used in the examples and comparative examples of the present invention are conventional commercially available products. The sources of experimental materials and instrument information used in the present invention are shown in Table 1 below:
[0073] Table 1
[0074]
[0075]
[0076]
[0077] Example 1 Preparation of hemostatic nanohydrogel particles
[0078] Example 1-1
[0079] 1. Preparation of Aminated Dendritic Mesoporous Silica Nanoparticles
[0080] 0.5g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in an emulsion system consisting of 70mL H2O, 0.8mL NH4OH, 15mL anhydrous ether and 5mL anhydrous ethanol. The emulsion was vigorously mixed using a magnetic stirrer and maintained at a stirring speed of 1000rpm for 0.5h to make the emulsion mixed evenly and stable. A mixture of 2.5mL tetraethoxysilane (TEOS) and 0.1mL 3-aminopropyltriethoxysilane (APTES) was quickly dropped into the emulsion, and after vigorous stirring for 4h at a stirring speed of 1000rpm, 1mL concentrated hydrochloric acid was added to stop the base-catalyzed reaction. Centrifugation at 2500-10000rpm for 10min gave a white precipitate, which was amino dendritic mesoporous silica nanoparticles. The amino dendritic mesoporous silica nanoparticles were washed 3 times with anhydrous ethanol and deionized water, respectively, and dispersed in ethanol for storage. The CTAB in the aminated dendritic mesoporous silica nanoparticles was removed by extraction. The aminated dendritic mesoporous silica nanoparticles were fully dispersed in a mixed solution consisting of 15 ml of concentrated hydrochloric acid and 120 mL of anhydrous ethanol, and stirred at 70 ° C for 24 h. Centrifuged at 8000 rpm for 10 min and washed with deionized water 3 times. After freeze-drying the aminated dendritic mesoporous silica nanoparticles, about 700 mg of aminated dendritic mesoporous silica was obtained and stored for later use.
[0081] 2. Preparation of Aminated Dendritic Mesoporous Silica Nanoparticles Loaded with Thrombin
[0082] First, the effect of amino-modified dendritic mesoporous silica nanoparticles on the loading amount of thrombin was explored. 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, and 5 mg of porcine thrombin powder were weighed and mixed with 1 ml of pure water to prepare thrombin solutions with concentrations of 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, and 5 mg / mL, respectively. The thrombin solutions were mixed with 1 mg of amino-modified dendritic mesoporous silica powder, and the concentration change of porcine thrombin after solution loading was measured by BCA protein concentration determination kit. The content of porcine thrombin was calculated according to the volume, and the loading rate and encapsulation rate were calculated by substituting into the formula (loading rate = mass of porcine thrombin loaded / mass of silica nanoparticles loaded with porcine thrombin, encapsulation rate = mass of porcine thrombin loaded / mass of porcine thrombin used). The measurement results are as follows: Figure 2 As shown, the optimal loading rate of 39.62% is achieved at the ratio of 1:2.
[0083] Then, the preparation of aminated dendritic mesoporous silica nanoparticles loaded with porcine thrombin was carried out. 100 mg of aminated dendritic mesoporous silica nanoparticles were weighed and mixed with 200 mg of porcine thrombin in a mass ratio of 1:2. The particles were dissolved in 1 ml of pure water and ultrasonicated for 30 min at a power of 40 khz. The particles were stirred for 30 min. The aminated dendritic mesoporous silica nanoparticles were loaded with thrombin by electrostatic adsorption. The porcine thrombin concentration after solution loading was measured by a BCA protein concentration determination kit, and the porcine thrombin content was calculated according to the volume. 100 mg of aminated dendritic mesoporous silica nanoparticles were loaded with 66 mg of porcine thrombin, and the concentration (g / ml) of the porcine thrombin-loaded mesoporous silica nanoparticle solution was 16.6%.
[0084] 3. Preparation of GelMA Premix
[0085] Weigh 0.1 g of methacrylamide gelatin (GelMA) (with an amino substitution degree of 60%) and 2.5 mg of photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), dissolve them in 1 mL of pure water to prepare a GelMA premix solution, which contains GelMA with a concentration (g / ml) of 10% and LAP with a concentration (g / ml) of 0.25%.
[0086] 4. Preparation of Hemostatic Nanohydrogel Particles
[0087] The aminated dendritic mesoporous silica nanoparticle solution loaded with porcine thrombin was mixed with the GelMA premix in a volume ratio of 1:1, ultrasonicated for 30 minutes and stirred for 6 hours, and the supernatant was removed by centrifugation to separate the hemostatic nanohydrogel particles (aminated dendritic mesoporous silica precipitate loaded with porcine thrombin wrapped in the outer circle of GelMA). After excitation with 400-420nm blue light, aminated dendritic mesoporous silica loaded with porcine thrombin wrapped in blue light excited GelMA was obtained. The prepared hemostatic nanohydrogel particles were analyzed using a transmission electron microscope of model HT7700, as shown in FIG. Figure 1 As shown in Figure 4, A is an amino dendritic mesoporous silica nanoparticle; B is an amino dendritic mesoporous silica nanoparticle loaded with thrombin; C is an amino dendritic mesoporous silica loaded with thrombin wrapped with GelMA; D is an amino dendritic mesoporous silica loaded with thrombin wrapped with GelMA after blue light excitation. As can be seen from Figure D, the prepared hemostatic nanohydrogel particles are dendritic spherical particles with an outer circle wrapped with GelMA, and the diameter is about 100-200nm.
[0088] The prepared hemostatic nano-hydrogel particles were measured by Zeta potential analyzer, and it was found that thrombin was negatively charged, the amino-modified dendritic mesoporous silica was positively charged, the amino-modified dendritic mesoporous silica loaded with thrombin was negatively charged, and GelMA was negatively charged. The amino-modified dendritic mesoporous silica loaded with thrombin and GelMA had a greater negative charge, proving that the material was successfully prepared. The Zeta potential diagram is shown in the figure. Figure 3 shown.
[0089] Example 1-2
[0090] 1. Preparation of Spherical Mesoporous Silica Nanoparticles
[0091] 0.5g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in an emulsion system consisting of 70mL H2O, 0.8mL NH4OH, 15mL anhydrous ether and 5mL anhydrous ethanol. The emulsion was vigorously mixed using a magnetic stirrer and maintained at a stirring speed of 1000rpm for 0.5h to make the emulsion mixed evenly and stable. 2.5mL of tetraethoxysilane (TEOS) was quickly dropped into the emulsion, and after vigorous stirring for 4h at a stirring speed of 1000rpm, 1mL of concentrated hydrochloric acid was added to stop the base-catalyzed reaction. Centrifugation at a speed of 2500-10000rpm for 10min gave 1g of white precipitate, which was spherical mesoporous silica nanoparticles.
[0092] 2. Preparation of Spherical Mesoporous Silica Nanoparticles Loaded with Thrombin
[0093] Weigh 80 mg of spherical mesoporous silica nanoparticles and mix them with 180 mg of bovine thrombin solution in a mass ratio of 1:2.3. Ultrasound for 25 minutes at an ultrasonic power of 45 khz, stir for 25 minutes, and load the spherical mesoporous silica nanoparticles with bovine thrombin through electrostatic adsorption. The bovine thrombin concentration after solution loading is measured by the BCA protein concentration determination kit, and the bovine thrombin content is calculated according to the volume. 80 mg of spherical mesoporous silica nanoparticles are loaded with 40 mg of bovine thrombin, and the concentration (g / ml) of the spherical mesoporous silica nanoparticle solution loaded with bovine thrombin is 12%.
[0094] 3. Preparation of GelMA Premix
[0095] Weigh 0.05 g of methacrylamide gelatin (GelMA) (with an amino substitution degree of 30%) and 1 mg of photoinitiator 2-hydroxy-40-(2-hydroxyethoxy)-2-methylpropenoate (IC-2959), dissolve them in 1 ml of phosphate buffer to prepare a GelMA premix solution, which contains 5% GelMA at a concentration (g / ml) and 0.1% IC-2959 at a concentration (g / ml).
[0096] 4. Preparation of Hemostatic Nanohydrogel Particles
[0097] After the spherical mesoporous silica nanoparticles loaded with bovine thrombin were mixed with the GelMA premixed solution in a volume ratio of 1:1, ultrasonic treatment was performed for 25 minutes at a power of 45 khz, and stirring was performed for 7 hours. The supernatant was removed by centrifugation to separate the hemostatic nanohydrogel particles (spherical mesoporous silica solution loaded with bovine thrombin wrapped by the outer circle GelMA). After white light excitation with a wavelength of 300 to 500 nm, spherical mesoporous silica nanoparticles loaded with bovine thrombin wrapped by white light excitation were obtained.
[0098] Examples 1-3
[0099] 1. Preparation of Dendritic Mesoporous Silica Nanoparticles
[0100] Tetraethyl orthosilicate (TEOS) was dissolved in cyclohexane as a silicon source as the upper oil phase, CTAB was used as a template and triethanolamine (TEA) was dissolved in water as the lower water phase to construct an oil-water two-phase stratification system. 36 ml of water, 24 ml of 25 wt.% CTAB and 0.18 g of triethanolamine were added to a 100 ml single-mouth round-bottom flask, and gently stirred at an oil bath temperature of 60 ° C. After one hour, 20 ml of 20 vv.% tetraethyl orthosilicate cyclohexane solution was carefully added to the upper layer of the water phase. Continue to maintain a temperature of 60 ° C and stir slowly. The standard is that the lower water phase is evenly stirred and the upper oil phase is basically still. The reaction is carried out under this condition for 12 hours. After 12 hours, the water phase is centrifuged at 15000 rpm for 30 minutes, the product is collected, and dispersed in an ethanol solution, and extracted at 60 ° C for 3 times, each time for 12 hours, to remove the surfactant CTAC. Finally, the obtained precipitate was washed three times with ethanol and deionized water respectively, centrifuged and dried under vacuum at room temperature to obtain dendritic mesoporous silica nanoparticles.
[0101] 2. Preparation of Thrombin-loaded Dendritic Mesoporous Silica Nanoparticles
[0102] Weigh 86 mg of dendritic mesoporous silica nanoparticles and mix them with 210 mg of porcine thrombin solution, the mass ratio of the two is 1:2.4, ultrasonic for 35 minutes, the ultrasonic power is 40 khz, and stirring is 35 minutes. The dendritic mesoporous silica nanoparticles are loaded with porcine thrombin by electrostatic adsorption. The porcine thrombin concentration after solution loading is measured by the BCA protein concentration determination kit, and the porcine thrombin content is calculated according to the volume. 86 mg of dendritic mesoporous silica nanoparticles are loaded with 50 mg of porcine thrombin, and the concentration (g / ml) of the dendritic mesoporous silica nanoparticle solution loaded with porcine thrombin is 13.6%.
[0103] 3. Preparation of GelMA Premix
[0104] 0.06 g of methacrylamide gelatin (GelMA) (with an amino substitution degree of 90%) and 1.6 mg of photoinitiator 2,2'-azo[2-methyl-n-(2-hydroxyethyl)propionamide (VA086)) were weighed and dissolved in 1 ml of normal saline to prepare a GelMA premix solution, which contained a GelMA concentration (g / ml) of 6% and a VA086 concentration (g / ml) of 0.16%.
[0105] 4. Preparation of Hemostatic Nanohydrogel Particles
[0106] The dendritic mesoporous silica nanoparticles loaded with porcine thrombin were mixed with the GelMA premixed solution at a volume ratio of 1:1, ultrasonicated for 35 minutes at an ultrasonic power of 40 khz, and stirred for 6 hours overnight, and the supernatant was removed by centrifugation to separate the hemostatic nanohydrogel particles (spherical mesoporous silica solution loaded with porcine thrombin wrapped in the outer circle of GelMA). After excitation by ultraviolet light with a wavelength of 200 to 400 nm, the dendritic mesoporous silica nanoparticles loaded with porcine thrombin wrapped in GelMA excited by ultraviolet light were obtained.
[0107] Examples 1-4
[0108] 1. Preparation of Hollow Mesoporous Silica Nanoparticles
[0109] First, 1.6 mL of ammonia water was added to a mixture of 71.4 mL of anhydrous ethanol and 1.6 mL of water. Then 2 mL of TEOS was added to the mixture and reacted at 400 rpm for 1 h at room temperature. After 1 h, the reaction solution was collected in a centrifuge tube and centrifuged at 10,000 rpm for 15 min, washed twice with ethanol and ultrapure water, and the resulting precipitate was resuspended in 40 mL of ultrapure water for later use.
[0110] Secondly, weigh 1.5g CTAB and 4.5mL water in a 250mL flask, then add 53.4μL triethanolamine and 60mL deionized water respectively, stir vigorously at 80℃ for 5min to completely dissolve, add 30mL of the above precipitation solution, continue stirring for 20min, add 450μL TEOS and continue stirring for 1h. After the reaction is completed, cool the solution to 50℃, take 5.67g anhydrous sodium carbonate, dissolve it in 9mL water, continue to react for 2h, then collect the solution in a centrifuge tube, centrifuge at 10000rpm for 15min, and wash it 3 times with anhydrous ethanol.
[0111] Finally, 1.5 g CTAB, 53.4 μL TEA and 64.5 mL water were stirred vigorously at 80 ° C to completely dissolve. Then 30 mL of the above SiO2 suspension was added, stirred continuously for 20 min, and then 450 μL TEOS was added, incubated for 1 h, cooled to 50 ° C, and then 9 mL of saturated Na2CO3 solution was added and reacted for 2 h. After the reaction, the solution was collected and centrifuged (10000 rpm, 15 min) to obtain hollow mesoporous silica nanoparticles.
[0112] 2. Preparation of thrombin-loaded hollow mesoporous silica nanoparticles
[0113] Weigh 94 mg of hollow mesoporous silica nanoparticles and mix them with 200 mg of human thrombin solution, the mass ratio of the two is 1:2.1, ultrasonic for 35 minutes, the ultrasonic power is 40 khz, and stirring is 35 minutes. The hollow mesoporous silica nanoparticles are loaded with human thrombin by electrostatic adsorption. The human thrombin concentration after solution loading is measured by the BCA protein concentration determination kit, and the content of human thrombin is calculated according to the volume. 94 mg of hollow mesoporous silica nanoparticles are loaded with 60 mg of human thrombin, and the concentration (g / ml) of the hollow mesoporous silica nanoparticle solution loaded with human thrombin is 15.4%.
[0114] 3. Preparation of GelMA Premix
[0115] Weigh 0.08 g of methacrylamide gelatin (GelMA) (with an amino substitution degree of 60%) and 2.0 mg of photoinitiator triethanolamine (TEA), dissolve them in 1 ml of pure water to prepare a GelMA premix solution, which contains 8% GelMA and 0.2% TEA in a concentration (g / ml).
[0116] 4. Preparation of Hemostatic Nanohydrogel Particles
[0117] After the hollow mesoporous silica nanoparticles loaded with human thrombin were mixed with the GelMA premixed solution at a volume ratio of 1:1, ultrasonic treatment was performed for 35 minutes at an ultrasonic power of 40 khz, and stirring was performed for 6 hours overnight. The supernatant was removed by centrifugation to separate the hemostatic nanohydrogel particles (hollow mesoporous silica nanoparticles loaded with human thrombin wrapped by the outer circle GelMA). After excitation by ultraviolet light with a wavelength of 200 to 400 nm, the ultraviolet-excited GelMA-wrapped hollow mesoporous silica nanoparticles loaded with human thrombin were obtained.
[0118] Examples 1-5
[0119] Compared with Example 1-1, N-vinyl caprolactam (VC) is used as the photoinitiator, and the rest is the same as Example 1-1.
[0120] Examples 1-6
[0121] Compared with Example 1-1, eosin-y (EY) is used as the photoinitiator, and the rest is the same as Example 1-1.
[0122] Examples 1-7
[0123] Compared with Example 1-1, the mesoporous silica nanoparticles are selected from the MCM series, and the rest are the same as Example 1-1.
[0124] Examples 1-8
[0125] Compared with Example 1-1, the mesoporous silica nanoparticles are selected from the SBA series, and the rest are the same as Example 1-1.
[0126] Examples 1-9
[0127] Compared with Example 1-1, the mesoporous silica nanoparticles are selected from the MSU series, and the rest are the same as Example 1-1.
[0128] Examples 1-10
[0129] Compared with Example 1-1, the mesoporous silica nanoparticles are selected from the TDU series, and the rest are the same as Example 1-1.
[0130] Experimental Example 1 Verification of the hemostatic effect of different hemostatic materials
[0131] The hemostatic ability of the hemostatic nano-hydrogel particles prepared in Example 1-1 was verified. Fresh rat blood containing sodium citrate anticoagulant was prepared, and 100 μL of blood samples were taken and placed in 4 mL centrifuge tubes, and then different materials were added for testing: (1) 50 μL of normal saline was added; (2) 50 μL of thrombin solution with the same loading amount as the hemostatic nano-hydrogel particles in Example 1-1 was added, and the mixture was allowed to stand for 30 seconds; (3) 50 μL of 100 mg / ml amino-modified dendritic mesoporous silica solution was added, and the mixture was allowed to stand for 30 seconds; (4) 50 μL of 100 mg / ml amino-modified dendritic mesoporous silica solution loaded with thrombin was added, and the mixture was allowed to stand for 30 seconds; (5) 50 μL of 100 mg / ml GelMA-coated amino-modified dendritic mesoporous silica solution loaded with thrombin was added at the same time, and irradiated with a 365 nm ultraviolet lamp for 30 seconds. The centrifuge tube was then inverted for observation. The results are as follows: Figure 4 As shown, A is a coagulation effect diagram after blood is mixed with physiological saline; B is a coagulation effect diagram after blood is mixed with thrombin solution; C is a coagulation effect diagram after blood is mixed with amino dendritic mesoporous silica; D is a coagulation effect diagram after blood is mixed with amino dendritic mesoporous silica loaded with thrombin; E is a coagulation effect diagram after blood is mixed with amino dendritic mesoporous silica loaded with thrombin wrapped in the outer ring GelMA and cross-linked with blue laser. In Figure E, after adding the amino dendritic mesoporous silica solution loaded with thrombin wrapped in GelMA and cross-linking with ultraviolet light, the blood forms a stable blood clot, and the liquid will not flow down after the centrifuge tube is inverted, proving that the hemostatic nanohydrogel particles prepared in Example 1-1 can quickly promote blood coagulation.
[0132] In order to study the mechanism of the hydrogel prepared in Example 1-1 promoting in vitro blood coagulation, a Hitachi S-3400N scanning electron microscope was used for observation. The method is as follows:
[0133] Each group of blood clots was fixed with 2.5% glutaraldehyde solution by volume for 2-3 hours, and then dehydrated with 30%, 50%, 70%, 90%, and 100% ethanol solutions diluted with pure water, three times for 10 minutes each time. Then, the water and ethanol were replaced with tert-butyl alcohol solution, and the replacement was performed three times for 10 minutes each time. Finally, the treated samples were sprayed with gold and observed with a scanning electron microscope.
[0134] The results are as follows Figure 5As shown, A is a scanning electron micrograph of a blood clot formed after mixing blood with saline; B is a scanning electron micrograph of a blood clot formed after mixing blood with thrombin solution; C is a scanning electron micrograph of a blood clot formed after mixing blood with amino dendritic mesoporous silica; D is a scanning electron micrograph of a blood clot formed after mixing blood with amino dendritic mesoporous silica loaded with thrombin; E is a scanning electron micrograph of a blood clot formed after mixing blood with amino dendritic mesoporous silica loaded with thrombin wrapped in an outer ring of GelMA and then crosslinked by ultraviolet light. As can be seen from Figure E, the hemostatic nanohydrogel particles self-assemble into a fibrous mesh structure in the blood and entangle blood cells, proving that the hemostatic nanohydrogel can promote coagulation. Among them, thrombin can promote the generation of a large number of fibrin meshes, and the cross-linking of GelMA into a mesh further strengthens hemostasis.
[0135] Experimental Example 2 Verification of the hemostatic time of normal blood and patient blood by different hemostatic materials
[0136] The hemostatic nano-hydrogel particles prepared in Example 1-1 were used to verify the hemostatic time of normal blood and blood from patients with liver cirrhosis.
[0137] Normal human blood in the blood collection tube was added to the EP tube, and then 0.1M calcium chloride solution was added and mixed, wherein the volume ratio of blood to calcium chloride solution was 10:1. After mixing for 10 seconds, 50 μL of the above blood mixture was added to a 96-well plate, and then 20 μL of different materials in each group (control group, amino-modified dendritic mesoporous silica group, thrombin group, amino-modified dendritic mesoporous silica group loaded with thrombin, and amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA, the control group was normal saline, and the amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA needed to be illuminated with blue laser emission light), at 5s, 10s, 30s, 60s, 180s, 300s and 420s, the well plate was rinsed with normal saline to stop coagulation, the liquid was quickly aspirated and washed repeatedly until the solution became clear, indicating that all soluble blood components had been removed. If uniform clot formation was observed, the coagulation time was recorded and a statistical graph was drawn using origin. The significance level was set as follows: * means P < 0.05, indicating a significant difference; ** means P < 0.01, indicating an extremely significant difference; ns means no significant difference. Figure 6 As shown, A is a diagram showing the coagulation effect of different materials initiating coagulation; B is a statistical diagram showing the coagulation time of different materials.
[0138] Fresh blood from patients with cirrhosis was prepared. The blood from the blood collection tube was added to the EP tube, and then 0.1 M calcium chloride solution was added and mixed. The ratio of blood to calcium chloride solution was 10:1. After mixing for 10 seconds, 50 μL of the blood mixture was added to a 96-well plate, and then 20 μL of the sample solutions of different materials in each group (control group, amino-modified dendritic mesoporous silica group, thrombin group, amino-modified dendritic mesoporous silica group loaded with thrombin, and The amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA, and the control group was saline. The amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA needed to be illuminated with a blue laser emission light). At time intervals of 5s, 10s, 30s, 60s, 180s, 300s, 420s and 480s, the well plate was rinsed with saline to stop coagulation. The liquid was quickly aspirated and repeatedly washed until the solution became clear, indicating that all soluble blood components had been removed. If a uniform clot was observed to form, the coagulation time was recorded and a statistical graph was drawn using origin. The significance level was set as follows: * means P < 0.05, indicating a significant difference; ** means P < 0.01, indicating an extremely significant difference; ns means no significant difference. The results are shown in Figure 7 As shown, A is a graph showing the coagulation effect of different materials initiating coagulation; B is a statistical graph showing the coagulation time of different materials. Figure 6 and Figure 7 It can be seen that for the hemostasis time of normal blood and blood from patients with cirrhosis, the initiation of coagulation time of the hemostatic nanohydrogel particle group is significantly earlier than that of the thrombin group, indicating that the hemostatic nanohydrogel particles have rapid and efficient hemostasis ability for both normal blood and blood from patients with cirrhosis.
[0139] Experimental Example 3 pH tolerance of hemostatic nanohydrogel particles and their ability to protect thrombin activity
[0140] 100 mg of each group of different materials (thrombin group, amino-modified dendritic mesoporous silica group loaded with thrombin, and amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA, the amino-modified dendritic mesoporous silica group loaded with thrombin and GelMA needs to be illuminated with blue laser light) were mixed with 1 ml of simulated gastric fluid and 1 ml of simulated intestinal fluid, respectively, and the mixing time was 5s, 10s, 30s, 60s, 3min, 5min, 10min, 30min, 60min, and then the mixture was added to a test tube containing 100 μL of fresh blood containing sodium citrate anticoagulant, and allowed to stand for 30s, and then the centrifuge tube was inverted for observation. The results are as follows Figure 8As shown in the figure, A is a graph of the coagulation effect of different materials after being treated with simulated gastric juice; B is a graph of the coagulation effect of different materials after being treated with simulated intestinal juice. The hemostatic nanohydrogel particle group still maintained a certain coagulation effect in the simulated gastric juice for 60 minutes, while the coagulation effect of the thrombin group completely failed at 5 minutes. The coagulation effect of the hemostatic nanohydrogel particle group and the thrombin group in the simulated intestinal juice did not decrease significantly. This shows that this hemostatic nanohydrogel particle can effectively resist the degradation of artificial gastric juice and small intestinal juice, and has the potential to be used for hemostasis of the digestive tract mucosa in vivo.
[0141] Experimental Example 4 Hemostatic Nanohydrogel Particles for Mouse Liver Hemostasis
[0142] The experimental unit is: Department of Gastroenterology Laboratory, The Second Affiliated Hospital of Army Medical University, and the experimental batch number is: AMUWEC20235153.
[0143] Normally raised 20-25g mice were anesthetized with 1% pentobarbital solution prepared with physiological saline, and then the liver was exposed, and part of the liver lobe was cut off with tissue scissors to construct a liver bleeding model, and then 100 μL of thrombin solution and 100 μL of hemostatic nanohydrogel particles in Example 1-1 were added dropwise with a pipette at the same time, and irradiated with 405nm blue laser for 30s. The control was not treated, and the wound bleeding was observed and photographed for record.
[0144] The results are as follows Fig. 9 As shown in the figure, A is an untreated wound; B is a wound after applying thrombin solution; C is a wound after applying hemostatic nano-hydrogel particles and UV cross-linking treatment; DF is a scanning electron microscope result of the ex vivo liver tissue wound specimen after hemostasis. Figures AC show that the hemostatic nano-hydrogel group has the best hemostatic effect. DF shows that there is no fibrin network in the control group; there is only a fibrin network in the thrombin group; the fibrin network structure and the methacrylamide-based gelatin in the blood clot of the hemostatic nano-hydrogel particle group are cross-linked into a network structure and wrapped together to form a complex.
[0145] Experimental Example 5 Hemostatic Nano-Hydrogel Particles Used for Hemostasis in Miniature Pigs Under Endoscopy with Blue Laser
[0146] Experimental unit: Department of Gastroenterology, the Second Affiliated Hospital of Army Medical University, experimental batch number: AMUWEC20235153.
[0147] An endoscope of model FUJIFILM (EG-L590ZW) was used as a device for injecting the hydrogel hemostatic agent of Example 1-1, and the blue laser light source of the endoscope was used as the irradiation light source. First, a miniature pig acute non-varicose upper gastrointestinal bleeding model was constructed by clamping part of the mucosal layer of the esophagus, stomach, and duodenum, and 1.5 mL of 100 mg / ml hemostatic nanohydrogel particle solution was injected into the wound bleeding site using a single-pass laparoscope catheter, and irradiated using the blue laser mode.
[0148] The results are as follows Fig.10 As shown, A is a hemostatic effect diagram for esophageal bleeding, B is a hemostatic effect diagram for gastric bleeding, and C is a hemostatic effect diagram for duodenal bleeding. Endoscopically, it can be observed that the hemostatic nano-hydrogel particles are attached to the wounds of the esophagus, stomach, and duodenum, respectively. The blue laser irradiation has stopped bleeding and formed a stable blood clot in less than 30 seconds, effectively blocking the bleeding site and significantly reducing the amount of bleeding. After 5 minutes of observation, there is no active bleeding in the wound. After flushing, the blood clots formed by the nano-hydrogel particles and blood are still firmly attached to the bleeding site, indicating that the hydrogel of the present invention can achieve visual hemostasis under blue laser endoscopy, and quickly and effectively block gastrointestinal mucosal bleeding.
[0149] Experimental Example 6 Verification of the Storage Time of Hemostatic Nanohydrogel Particles
[0150] The hemostatic nano-hydrogel particles were freeze-dried and stored in a 4°C refrigerator. After 45 days of storage, they were prepared into a 100 mg / mL solution with pure water. 100 μL of fresh blood from rats was collected in a 4 mL centrifuge tube, and 50 μL of the hemostatic nano-hydrogel particle solution was added and irradiated with a 365 nm ultraviolet lamp for 30 seconds. The centrifuge tube was then placed upside down for observation. Fig.12 As shown, the blood coagulates and does not flow down along the tube wall, verifying that the hemostatic nanohydrogel particles can maintain thrombin activity for ≥45 days.
[0151] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. A hemostatic nano hydrogel particle, characterized in that: The hemostatic nano hydrogel particles are prepared by using the following raw materials in parts by weight: 40-50 parts of mesoporous silica nanoparticles, 20-33 parts of thrombin, 25-50 parts of methacrylamide-based gelatin and 0.5-1.25 parts of a photoinitiator.
2. The hemostatic nano-hydrogel particles according to claim 1, characterized in that: The hemostatic nano hydrogel particles are prepared by using the following raw materials in parts by weight: 43-47 parts of mesoporous silica nanoparticles, 25-30 parts of thrombin, 30-40 parts of methacrylamide-based gelatin and 0.8-1 part of a photoinitiator.
3. The hemostatic nano hydrogel particles according to claim 1 or 2, characterized in that: The mesoporous silica nanoparticles are selected from one of spherical mesoporous silica nanoparticles, dendritic mesoporous silica nanoparticles and hollow mesoporous silica nanoparticles; And / or, the mesoporous silica nanoparticles are selected from one of the MCM series, SBA series, MSU series and TDU series; Preferably, the mesoporous silica nanoparticles are selected from amino-modified dendritic mesoporous silica nanoparticles.
4. The hemostatic nano-hydrogel particle according to any one of claims 1 to 3, characterized in that: The thrombin is selected from one of porcine thrombin, bovine thrombin and human thrombin; Preferably, the hemostatic nano-hydrogel particles can maintain thrombin activity for ≥45 days.
5. The hemostatic nano-hydrogel particle according to any one of claims 1 to 4, characterized in that: The amino substitution degree of the methacrylamide-based gelatin is 30-90%; Preferably, the amino substitution degree of the methacrylamide-based gelatin is 60-90%.
6. The hemostatic nano-hydrogel particle according to any one of claims 1 to 5, characterized in that: The photoinitiator is selected from one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-40-(2-hydroxyethoxy)-2-methylpropenone (IC-2959), 2,2'-azo [2-methyl-n-(2-hydroxyethyl) propionamide (VA086), triethanolamine (TEA), N-vinyl caprolactam (VC) and eosin-y (EY); Preferably, the photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
7. The hemostatic nano-hydrogel particle according to any one of claims 1 to 6, characterized in that: The triggering light source of the hemostatic nano hydrogel particles is a blue laser with a wavelength of 395-425nm, a white light with a wavelength of 300-760nm, or an ultraviolet light with a wavelength of 200-400nm; Preferably, the triggering light source of the hemostatic nano-hydrogel particles is a blue laser with a wavelength of 395-425 nm.
8. A method for preparing the hemostatic nano hydrogel particles according to any one of claims 1 to 7, the method comprising the following steps: (1) mixing mesoporous silica nanoparticles and thrombin and dissolving them in pure water, and then performing ultrasonic treatment and stirring treatment to obtain a mesoporous silica nanoparticle solution loaded with thrombin; (2) dissolving methacrylamide-based gelatin and a photoinitiator in a solvent to obtain a GelMA premix; (3) The thrombin-loaded mesoporous silica nanoparticle solution is mixed with the GelMA premix, and the mixture is stirred after ultrasonic treatment, and the precipitate is collected by centrifugation to obtain hemostatic nano-hydrogel particles.
9. The method for preparing hemostatic nano-hydrogel particles according to claim 8, wherein in step (1), the concentration (g / ml) of the mesoporous silica nano-particle solution loaded with thrombin is 12-16.6%; Preferably, the concentration (g / ml) of the thrombin-loaded mesoporous silica nanoparticle solution is 13.6-15.4%; Further preferably, the mesoporous silica nanoparticles and thrombin are mixed in a mass ratio of 1:(2-2.44).
10. The method for preparing hemostatic nano-hydrogel particles according to claim 8 or 9, wherein in step (1), the ultrasonic treatment time is 25-35 min; and / or, the power of ultrasound is 40-45 khz; Preferably, the stirring time is 25-35 min.
11. The method for preparing hemostatic nano-hydrogel particles according to any one of claims 8 to 10, wherein in step (2), the solvent is selected from one of pure water, physiological saline and phosphate buffer.
12. The method for preparing hemostatic nano-hydrogel particles according to any one of claims 8 to 11, wherein in step (2), the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 5-30%; Preferably, the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 5-10%; More preferably, the concentration (g / ml) of methacrylamide-based gelatin in the GelMA premix is 6-8%.
13. The method for preparing hemostatic nano-hydrogel particles according to any one of claims 8 to 12, wherein in step (2), the concentration (g / ml) of the photoinitiator in the GelMA premix is 0.10%-0.40%; Preferably, the concentration (g / ml) of the photoinitiator in the GelMA premix is 0.16-0.25%.
14. The method for preparing hemostatic nano-hydrogel particles according to any one of claims 8 to 13, wherein in step (3), the mesoporous silica nanoparticle solution loaded with thrombin is mixed with the GelMA premix solution in a volume ratio of 1:2 to 2:1; Preferably, the mesoporous silica nanoparticle solution loaded with thrombin is mixed with the GelMA premix solution in a volume ratio of 1:1; Further preferably, the ultrasonic treatment time is 25-35 min; and / or, the power of ultrasound is 40-45 khz; More preferably, the stirring time is 6-7h.
15. Hemostatic nano-hydrogel particles prepared by the method for preparing hemostatic nano-hydrogel particles according to any one of claims 8 to 14.
16. A hemostasis system, characterized in that: The hemostatic system comprises the hemostatic nano-hydrogel particles according to any one of claims 1 to 7 or 15, a hemostatic nano-hydrogel particle injection device and a triggering light source generating device.
17. The hemostasis system according to claim 16, characterized in that: The hemostatic nano-hydrogel particle injection device comprises a syringe and a digestive endoscope channel; Preferably, the triggering light source generating device includes a blue laser emitting lamp, a blue laser endoscope, a narrow-band imaging endoscope and an ultraviolet light emitting lamp.
18. Use of the hemostatic nano hydrogel particles according to any one of claims 1 to 7 or 15 in the preparation of hemostatic materials or drugs.
19. Use of the hemostatic nano hydrogel particles according to any one of claims 1 to 7 or 15 in preparing organ hemostatic materials or drugs.
20. The use according to claim 19, characterized in that The organ is a solid organ or a hollow organ; Preferably, the solid organ is heart, liver, spleen, lung, pancreas or kidney; More preferably, the hollow organ is the esophagus, stomach, duodenum, jejunum, ileum or colon.
Citation Information
Cited By
Calcipotriol compound, difunctional integrated hydrogel for treating psoriasis as well as preparation and application of difunctional integrated hydrogel
CN121445897A
Calcipotriol complex, bifunctional monolithic hydrogel for treating psoriasis, its preparation and application
CN121445897B